Ensaio sobre o agente racional: esparadrapos para um paciente terminal? - Moura, David Miranda de (2007)
The Rational Agent model have been a foundational basis for theoretical models such as Economics, Management Science, Artificial Intelligence and Game Theory, mainly by the ¿maximization under constraints¿ principle, e.g. the ¿Expected Utility Models¿, among them, the Subjective Expected Utility (SEU) Theory, from Savage, placed as most influence player over theoretical models we¿ve seen nowadays, even though many other developments have been done, indeed also in non-expected utility theories field. Having the ¿full rationality¿ assumption, going for a less idealistic sight ¿bounded rationality¿ of Simon, or for classical anomalies studies, such as the ¿heuristics and bias¿ analysis by Kahneman e Tversky, ¿Prospect Theory¿ also by Kahneman & Tversky, or Thaler¿s Anomalies, and many others, what we can see now is that Rational Agent Model is a ¿Management by Exceptions¿ example, as for each new anomalies¿s presentation, in sequence, a ¿problem solving¿ development is needed. This work is a theoretical essay, which tries to understand: 1) The rational model as a ¿set of exceptions¿; 2) The actual situation unfeasibility, since once an anomalie is identified, we need it¿s specific solution developed, and since the number of anomalies increases every year, making strongly difficult to manage rational model; 3) That behaviors judged as ¿irrationals¿ or deviated, by the Rational Model, are truly not; 4) That¿s the right moment to emerge a Theory including mental processes used in decision making; and 5) The presentation of an alternative model, based on some cognitive and experimental psychology analysis, such as conscious and uncounscious processes, cognition, intuition, analogy-making, abstract roles, and others. Finally, we present conclusions and future research, that claims for deeper studies in this work¿s themes, for mathematical modelling, and studies about a rational analysis and cognitive models possible integration. .